Markov-regime switching in economic variables: Part I. Modelling, estimating and testing. - Part II. A selective survey - Sylvia Kaufmann; Martin Scheicher (Institute for Advanced Studies (IHS), 1996)
Modelling the growth rate of economic time series with a Markov switching process in their mean and/or their variance allows to take account of two facts that are often encountered in such series, namely that the periods in which each mean is prevailing differ in their duration and that the variance of the time series differ in each period. In a first part, we will motivate the class of regime switching models, and revue the estimating and testing procedures. In the second part, we will present a brief survey of the literature on regime switching models and their applications, and also present first results of actual own research.
Keywords: C12; C13; C22; C63; E32; G14; 330; Markov switching; time series; EM-agorithm; empirical processes; macroeconomics; finance